2015
DOI: 10.1055/s-0035-1549993
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Mitiglinide/Voglibose Fixed-dose Combination and Glimepiride in Modifying Low-density Lipoprotein Heterogeneity in Japanese Type-2 Diabetic Patients: A Pilot Study

Abstract: Purpose: The purpose of this study was to compare the effects of mitiglinide/voglibose fixed-dose combination and glimepiride on low-density lipoprotein (LDL)-heterogeneity in type-2 diabetic patients with unstable glycemic control after treatment with dipeptidyl peptidase-4 (DPP-4) inhibitors. Methods: This was an open-label pilot study in which type-2 diabetic patients were randomly assigned to the mitiglinide/voglibose (fixed-dose combination of mitiglinide 10?mg and voglibose 0.2?mg, n=14) or glimepiride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…22,26 Voglibose has been considered safe (due to poor absorption after oral use) and effective as a monotherapy or a combination therapy. 23,[27][28][29][30][31][32][33] In one study, voglibose was found to be effective in lowering daily glycemic excursions, HbA1c, and plasma glucose levels and also in improving insulin sensitivity in T2DM patients. 34 In clinical management, physicians usually prefer to prescribe combination therapies instead of a monotherapy, particularly if the target glycemic goal is not achieved with monotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…22,26 Voglibose has been considered safe (due to poor absorption after oral use) and effective as a monotherapy or a combination therapy. 23,[27][28][29][30][31][32][33] In one study, voglibose was found to be effective in lowering daily glycemic excursions, HbA1c, and plasma glucose levels and also in improving insulin sensitivity in T2DM patients. 34 In clinical management, physicians usually prefer to prescribe combination therapies instead of a monotherapy, particularly if the target glycemic goal is not achieved with monotherapy.…”
Section: Introductionmentioning
confidence: 99%